Collaboration between predators and weak Allee effect in prey. Consequences on the dynamics of a predation model - González-Olivares, Eduardo (2022)
The interactions between predators and their prey in the real world are usually affected by diverse ecological phenomena acting on both the prey and the predators. Collaboration or cooperation between predators is one of those behaviors, which has received less attention from researchers than competition among consumers. These contacts are important aspects of the dynamics of food chains and trophic webs. In this work, we will study the influence of collaboration or cooperation (hunting cooperation) between predators to consume (or capture) their favorite prey, which are affected by an effect Allee weak. We extend the results obtained in a previously published model, considering only collaboration between predators and in which the Allee effect is absent.